Antibacterial and Antibiofilm Efficacy of Pineapple Hump (Ananas comosus) on Porphyromonas gingivalis in vitro - Soulissa, Abdul Gani; Lombardo, Billy; Widyarman, Armelia Sari (UI Scholars Hub, 2021)
Background: Periodontal disease is one of the most prevalent oral health problems in Indonesia that affects supporting tissues of the teeth. Porphyromonas gingivalis plays an important role in the pathogenesis of periodontal disease. Alternative therapy with natural plant extracts, including pineapple (Ananas comosus) hump extract may inhibit the growth of bacteria that cause periodontal disease. Objective: To determine the effect of pineapple hump extract on bacterial growth and adhesion of Porphyromonas gingivalis biofilms. Method: The bacterial inhibition test was performed by the agar well diffusion method, and biofilm density measurements were made using the biofilm assay method. Results: Pineapple hump extract can inhibit bacterial growth optimally at a concentration of 100%, with an average zone of inhibition of 7.3 mm. The extract at a 50% concentration can eradicate the biofilms in a 6 h incubation time with an average OD of 0.124. The Shapiro-Wilk method confirmed a normal distribution of the data. Both one-way ANOVA and post hoc test showed a significant difference between the inhibitory ability of pineapple hump extract and between concentrations to restrict formation of Porphyromonas gingivalis biofilms. Conclusion: Pineapple hump extract was able to inhibit bacterial growth and eradicate the adhesion of Porphyromonas gingivalis biofilms in vitro.